Biodiesel Production Process Optimization from Sugar Apple Seed Oil (Annona squamosa) and Its Characterization - Hotti, Siddalingappa R.; Hebbal, Omprakash D. (Journal of Renewable Energy, 2015)
This paper presents the production of biodiesel from nonedible, renewable sugar apple seed oil and its characterization. The studies were carried out on transesterification of oil with methanol and sodium hydroxide as catalyst for the production of biodiesel. The process parameters such as catalyst concentration, reaction time, and reaction temperature were optimized for the production of sugar apple biodiesel (SABD). The biodiesel yield of 95.15% was noticed at optimal process parameters. The fuel properties of biodiesel produced were found to be close to that of diesel fuel and also they meet the specifications of ASTM standards.